2020
DOI: 10.1021/acsami.0c13669
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Space Charge at Nanoscale in Dielectric Polymer Nanocomposites

Abstract: Heterogeneous dielectric materials such as dielectric polymer nanocomposites have attracted extensive attention because of their exceptional insulating and dielectric performance, which originates from the unique space charge dynamics associated with the various interfacial regions. However, the space charge distribution and transport in polymer nanocomposites remain elusive due to the lack of analytical methods that can precisely probe the charge profile at the nanoscale resolution. Although a few studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
0
40
0
1
Order By: Relevance
“…As a result, adding a small amount of nanofillers into polymer can lead to a dramatic improvement in mechanical, thermal, electrical, and optical properties, while maintaining the low mass density and good processability inherent to the polymer. 2,3,6,8 In addition, the incorporation of nanoparticles can also introduce new functionalities (e.g., conductivity 3 ) that are absent in the pristine polymer matrix, which further extends the utility of the constituted nanocomposites. Thus, designing PNCs offers a versatile strategy for preparing highperformance and cost-effective materials, which find broad applications in materials, energy storage, and biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, adding a small amount of nanofillers into polymer can lead to a dramatic improvement in mechanical, thermal, electrical, and optical properties, while maintaining the low mass density and good processability inherent to the polymer. 2,3,6,8 In addition, the incorporation of nanoparticles can also introduce new functionalities (e.g., conductivity 3 ) that are absent in the pristine polymer matrix, which further extends the utility of the constituted nanocomposites. Thus, designing PNCs offers a versatile strategy for preparing highperformance and cost-effective materials, which find broad applications in materials, energy storage, and biomedical fields.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites (PNCs), formed by dispersing nanoparticles in a polymer matrix, have drawn substantial attention from both industry and academia in past decades. Compared to traditional fillers, nanofillers, reducing the object size, significantly increase the interfacial area between fillers and polymer that efficiently modifies the matrix properties. As a result, adding a small amount of nanofillers into polymer can lead to a dramatic improvement in mechanical, thermal, electrical, and optical properties, while maintaining the low mass density and good processability inherent to the polymer. ,,, In addition, the incorporation of nanoparticles can also introduce new functionalities (e.g., conductivity) that are absent in the pristine polymer matrix, which further extends the utility of the constituted nanocomposites. Thus, designing PNCs offers a versatile strategy for preparing high-performance and cost-effective materials, which find broad applications in materials, energy storage, and biomedical fields. ,,, However, due to the complex nature of PNCs as multicomponent systems, the corresponding control parameter space is large.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Takada proposed a multiregion structure model of nanocomposite dielectrics . According to this model, nanoparticles introduce trap sites at the polymer matrix–nanoparticle interface, which can hinder the movement of high-energy electrons and the development of breakdown paths, as well as increase the dielectric strength. For instance, Li et al reported the charge mobility and dielectric strength of a nano-Al 2 O 3 -filled polymer, which was capable of dispersing the applied electric field throughout the polymer matrix and preventing the propagation of breakdown channels, thereby resulting in the highest dielectric strength and lowest leakage current in polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interphase properties remain challenging to characterize Polymers 2021, 13,1936 2 of 13 and their impact on NC ones are, consequently, poorly understood. To characterize interphase properties at the local scale, techniques derived from the Atomic Force Microscopy (AFM) were used: the Peak Force Quantitative NanoMechanical (PF-QNM) mode for the interphase mechanical properties and dimension determination [25,26], the Electrostatic Force Microscopy (EFM) mode for the dielectric permittivity [27][28][29], and the Kelvin Probe Force Microscopy (KPFM) for space charge measurements [30,31]. All of these existing studies only provide an interphase characterization at room temperature and a partial description of dielectric properties as some assumptions are requested for their entire determination.…”
Section: Introductionmentioning
confidence: 99%